Issues of ecological and economical sustainability of fish culture in the southern hydrological basin of lake Balaton - Hancz, Csaba; Nagy, Zoltán; Gál, Dénes; Varga, Dániel (Acta Agraria Kaposváriensis, 2015)
Lake Balaton - as the biggest natural lake in Central Europe - has an extended drainage basin (5180 km2). In the southern part of this basin 235 water bodies can be found, most of them (220) are used as fish ponds while the remaining serve for angling (15) and for water storage (1). The aim of this study was surveying this vulnerable area from the main viewpoints of sustainability. GPS based survey of the area revealed that update of the official database is highly recommended, moreover a significant part of ponds is already covered by macrovegetation. Generally applied semi-intensive pond fish culture is based on use of large quantities of organic matter input (cereal grains and manure) which does not cause environmental pollution during the growing season. Moderate water pollution may occur only in the autumn harvesting time however the almost total use of water sources may negatively influence the water balance of the Lake Balaton. Feeding 2 – 3 t/ha cereals per growing season makes possible to obtain net yields around 600 kg/ha in fish ponds. This form of production is not sustainable for long neither from economic nor from environmental point of views. However one part of fish production serves restocking purposes (common carp and carnivorous species) which is indispensable for the management of Lake Balaton the presence of grass carp, silver carp and bighead carp in the production structure may be interpreted as constant hazard for the ichthyofauna of the lake.
Keywords: Lake Balaton; fish culture; sustainability; semi-intensive technology